Scattering Theory for Jacobi Operators with General Step-Like Quasiperiodic Background - Egorova, I.; Michor, J.; Teschl, G. (Журнал математической физики, анализа, геометрии, 2008)
We develop direct and inverse scattering theory for Jacobi operators with step-like coeffcients which are asymptotically close to different finite-gap quasiperiodic coeffcients on di erent sides. We give a complete characterization of the scattering data, which allow unique solvability of the inverse scattering problem in the class of perturbations with finite first moment.